Klebsiella pneumoniae Phage M198 and Its Therapeutic Potential - Lika Leshkasheli; Ia Kusradze; Darejan Bolkvadze; Lia Askilashvili; Maria Chichashvili; Giorgi Tsertsvadze; Elisabed Zaldastanishvili (Viruses)
The rapid worldwide spread of antibiotic resistance is quickly becoming an increasingly concerning problem for human healthcare. Non-antibiotic antibacterial agents are in high demand for many Gram-negative bacterial pathogens, including Klebsiella pneumoniae. Klebsiella-targeting phages are among the most promising alternative therapy options. They have already been successfully applied in a number of cases, and it is expected that the need for anti-Klebsiella phages will only increase in the future. This prospect highlights the need for well-characterized therapeutic phages. In this work, we describe a K. pneumoniae phage, which also infects strains of Klebsiella oxytoca. Here, we characterize phage M198 in terms of its biological and genetic properties. Since in some phage therapy cases, phages are administered in combination with antibiotics, here, we also screen for possible synergistic effects of combining phage M198 with six different antibiotics. We found that phage M198 has good lytic activity against clinical isolates; it does not have any indications of a temperate lifestyle, and it has synergistic potential when combined with some therapeutically relevant antibiotics.